An unstructured loop that is critical for interactions of the stalk domain of Drp1 with saturated phosphatidic acid. (2nd November 2018) - Adachi, Yoshihiro; Iijima, Miho; Sesaki, Hiromi
ABSTRACT: Dynamin-related protein 1 (Drp1) is a dynamin superfamily GTPase, which drives membrane constriction during mitochondrial division. To mediate mitochondrial division, Drp1 is recruited to the mitochondrial outer membrane and is assembled into the division machinery. We previously showed that Drp1 interacts with phosphatidic acid (PA) and saturated phospholipids in the mitochondrial membrane, and this interaction restrains Drp1 in initiating the constriction of mitochondria. Here, we show that the role of saturated acyl chains of phospholipids is independent of their contribution to the membrane curvature or lipid packing suggesting their direct interaction with Drp1. We further show that an unstructured loop in the stalk domain of Drp1 is critical for interaction with unsaturated PA. Our data significantly advance our understanding of this unique protein-lipid interaction involved in mitochondrial division.